Chieftaincy Institutions among Yoruba Muslims in Nigeria: Between The Present And Past - Sulaiman, Kamal-deen Olawale (IIUC Studies, 2014)
This paper intends to analyse the contemporary issues and challenges of chieftaincy Institutions among Yoruba Muslims in Nigeria. It delves in to the origins of Islamic chieftaincy institutions, the roles and functions of Islamic Chieftaincy title holders. The methodology employed was based on information and analysis of the data from written sources. The paper reveals that, the need to encourage believers in the propagation of Islam is a major reason for the multiplicity of chieftaincy titles. The paper recommended that for Islamic chieftaincy titles to be meaningful, preference should be given to Muslims who have the fear of Allah. While it concluded that in the early history merit and not mediocrity was the major consideration in the award of chieftaincy titles. The current trend therefore requires urgent review. DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20411 IIUC Studies Vol.8 December 2011: 161-174